Relationship of Low Level of Ferritin in Newborn and Iron Deficiency Anemia in Mothers: A Single Center Study (Medical Forum Monthly, 2023)
Objective: To assess the relationship between low levels of ferritin in newborns and iron deficiency anemia in mothers.Study Design: current descriptive cross-sectional studyPlace and Duration of Study: This study was conducted at the HBS General Hospital Islamabad July 2022 to December 2022.Materials and Methods: Blood was taken and sent to laboratory for testing of serum ferritin. The data was collected through predesigned proforma. The collected data was analyzed by the latest version of SPSS.Results: The total number of participants was 160 in the present studies. The mean age was 25 ±1.98 years. 58 (36.25 %) had mild iron deficiency anemia, while 55 % of them had moderate, and 8.75% of them has severe iron deficiency anemia. Moreover, the proportion of serum ferritin in the newborn had a low level of 102 (63.75%) while 58 (25 %) had a normal level of serum ferritin.42 (41.17 %) had mild, 52 (50.98 %) moderate and 8 (7.85 %) of them had severe low serum ferritin levels.Conclusion: The present study concluded that most of the mothers with iron deficiency had low serum ferritin levels. Therefore, iron deficiency anemia and low level of serum ferritin serum in the infants of iron-deficient mothers is a serious health problem, and both mothers and infants can develop multiple health problems. Finally, the study concluded that iron-deficient mothers had a direct effect on the serum ferritin level of their infants.